Taxing home ownership: Distributional effects of including net imputed rent in taxable income - Francesco Figari; Alari Paulus; Holly Sutherland; Panos Tsakloglou; Gerlinde Verbist; Francesca Zantomio (University of Essex, Institute for Social and Economic Research (ISER), 2012)
Imputed rental income of homeowners is tax exempt in most countries, despite the long-standing arguments recommending its inclusion in the tax base, on both equity and efficiency grounds. The current fiscal crisis revived interest towards this form of taxation. The paper investigates the fiscal and distributional consequences of including homeowners' imputed rent, net of mortgage interest and maintenance costs, in taxable income as any cash income source that extends consumption opportunities. Three scenarios are analysed in six European countries: in the first imputed rent is included in the taxable income of homeowners, while at the same time existing mortgage interest tax relief schemes and taxation of cadastral incomes are abolished. In two further revenue-neutral scenarios, the additional tax revenue raised through the taxation of imputed rent is redistributed to taxpayers, either through a proportional rebate or a lump-sum tax credit. Results show how including net imputed rent in the tax base might affect inequality in each of the countries considered. Housing taxation appears to be a promising avenue for raising additional revenues, or lightening taxation of labour, with no inequality-increasing side-effects.
Keywords: D31; H23; I31; I32; 330; housing taxation; imputed rent; income distribution; inequality; microsimulation; Grundsteuer; Wohneigentum; Miete; Kalkulatorische Kosten; Steuerbemessung; Verteilungswirkung; Europa